"ISOC", International School of Organometallic Chemistry: A Success Story. Issue 11 (23rd March 2020) - Pettinari, Claudio
Abstract : Guest Editor Claudio Pettinari describes the organization of the first School of Organometallic Chemistry, telling the story of its development to become the highly successful International School anticipating its 13th edition in 2021. He then introduces the 24 contributions in this double Special Issue of EurJIC in celebration of the 12th edition.